Venture Capital and Growth of Young High-Tech Firms in the EU: A Systematic Review of the Empirical Evidence - Smaranda Pantea; Marcel Tkacik (Prague University of Economics and Business, Faculty of International Relations (FIR), 2021)
This study contributes to the debate on VC-related policies that aim to support the growth of young high-tech firms in the EU. The study provides a systematic review of the results of 22 firm-level studies that estimate causal effects of VC using counterfactual impact evaluation methods and data from 12 EU countries. The results show a large preponderance of positive effects of VC on employment, revenues and assets growth and on reducing financial constraints, but mixed effects on innovation and other aspects of firm performance. They suggest that private VC tends to have larger effects than government VC, but that the latter plays an important role as a complement to private VC. The review finds supporting evidence for the two main channels highlighted by the literature: provision of financial resources and of nonfinancial resources (know-how and networks), although the evidence on the latter is scarce. Based on the results of the review and on the current landscape of VC in the EU, the study highlights important gaps in the literature and policy implications.
Keywords: G24; L25; M13; O31; O33; O52; 330; venture capital; firm performance; start-ups; innovation; systematic literature review; European Union